Identification of Glibenclamide in Herbal Products Found in Medan Petisah - Cintiya, Puja Anggi; Sembiring, Novita Br; Syahputra, Hariyadi Dharmawan (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2025)
Glibenclamide is an antidiabetic drug that is not permitted for use in traditional herbal medicines because it can cause serious side effects such as hypoglycaemia and organ damage. This study aims to identify the presence of glibenclamide as a Chemicals Drug (CD) in antidiabetic herbal medicines found in Medan Petisah. Two herbal medicine samples, namely Unlabelled Powdered Herbal Medicine and JSR Diabetes Herbal Medicine (Jamu), were analysed using Fourier Transform Infrared Spectroscopy (FTIR). The infrared spectra of the samples were compared with the standard Glibenclamide spectrum to identify characteristic wavenumber patterns. The analysis results showed similarities in the patterns at 3280 cm⁻¹ (N–H bond), 2922 cm⁻¹ (C–H bond), and 1237–1282 cm⁻¹ (S=O bond), confirming the presence of Glibenclamide in both samples. These findings indicate a violation of Indonesian Minister of Health Regulation No. 007 of 2012, which prohibits the use of Chemicals Drug (CD) in traditional preparations. Therefore, this study recommends strict supervision of the distribution of antidiabetic herbal medicines and public education about the dangers of consuming herbal medicines containing CD to prevent health risks.